MSME Agglomeration and Image Branding Destinations in Tourism Village Development as an Economic Improvement for Rural Communities (Case Study at Sendang Senjoyo Tourism Object, Salatiga City) - Noviandari Sari Utami; Endang Susanti; Muhammad Sholeh (Yayasan Ilomata, 2022)
Sendang Senjoyo is a pond that has its own spring and has a beautiful view. Located in Tegalwaton Village, Tingkir District, Salatiga Regency, Central Java, making it a tourist location that promises to be natural beauty with a cool atmosphere with the freshness of cold and clear water making it a suitable tourist spot to unwind and relax with family. With the existence of this tourist attraction, it helps the economy of the surrounding community through MSMEs that stand at the tourist attraction. This research method uses a qualitative descriptive approach, the purpose of this research is to find out how the agglomeration of SMEs and Image Branding Destinations in Tourism Village Development as an Economic Improvement of Village Community with the focus of research on SMEs in the tourist attraction of Sendang Senjoyo, Salatiga. The resource persons taken in this study amounted to 4 people consisting of the Head of Tegalwaton Village, Semarang Regency, the tourism object manager (BUMDES) Sendang Senjoyo, MSME actors in Sendang Senjoyo and the surrounding community or tourists. The results of this study indicate the management of the Senjoyo tourist attraction is carried out by the Tegalwaton Village government in collaboration with the Village-Owned Enterprises (BUMDES) and local communities. Image Branding Destination Sendang Senjoyo tourist attraction was built with the concept of spiritual, nature, entertainment, tree museum and springs. The lack of facilities and infrastructure at the Senjang Senjoyo tourist attraction which is still not optimal and not functioning properly, as well as the absence of natural resource development for MSME actors to be given training in improving the ability to manage business. The arrangement of selling places at the Sendang Senjoyo tourist attraction is also still not neatly arranged and the development of merchant places is not evenly distributed because many permanent buildings still use wood and tarpaulin.